Realidade material e efetividade formal do eu absoluto - Emilia Agnes Assis de Lima (2007)
The text Sur la Possibilite d´une form de la Philosophie en général presents an introduction to the philosophical method proposed by Schelling in beginning of his philosophical career. In this text, the author introduces a series of specific concepts whose main function is to investigate the unfoldings of an unconditioned beginning of being and of thinking in a finite or conditioned reality. The concept of effectiveness itself is unfolded into two other concepts, namely Wirklichkeit and Realität, which represent either the unconditioned content of being and of thinking, or one of the conditioned ways in which that same beginning is expressed, thus consisting of anemblematic and key concept for the understanding of the structure of the philosophical method presented by Schelling in Sur la Possibilite d´une form de la Philosophie en 7 général as well as for the understanding of the own structure of the philosophical speech in the conception of F.W.J.Schelling.